Exploring Conventional Models of Purchase Intention: Consumer Attitudes Towards Smartphones Advertisement - Ahmad Azaini, Abdul Manaf; Lee, Sung Pil (Dongseo University, 2014)
Mobile phone makers compete for market shares through domination in media advertisements. These include domination of advertisements (Ads) in TV and the internet. However, the abundance and complexity of the competitions of Ads in TV does not guarantee advertising success which can influence consumers’ emotion and the purchase intention towards the brand. This research analyses the case of a directional model on Attitude-towards-the-Ad model as a baseline into a new proposed correlation models (MacKenzie, Scott, &Lutz,1989). The survey targets the involvements of Asian smartphone owners’ attitude on advertisements, brands and purchase intentions. CFA (Confirmatory factor Analysis) was used in the research experiments, including hypothesis testing, the outcome of model fit which revealed significant levels and were successful. The study revealed that all three paths have consistently high coefficient paths (Attitude to Ads – Attitude to Brands – Purchase Intention), showing significant value of (β=>.80), which supported each correlation factors. Therefore, this structural model, could set standards for creative managers and advertising teams to improve.